Asset management for blue-green infrastructures: a scoping review. Issue 2 (7th November 2022) - Langeveld, Jeroen G.; Cherqui, Frédéric; Tscheikner-Gratl, Franz; Muthanna, Tone Merete; Juarez, Marina Fernandez-Delgado; Leitão, Joao P.; Roghani, Bardia; Kerres, Karsten; do Céu Almeida, Maria; Werey, Caty; Rulleau, Bénédicte
Abstract: Urban drainage systems have developed way beyond the traditional piped combined or separate sewer systems. Many 'new' systems are being introduced, ranging from stormwater infiltration facilities to green roofs. However, the widely advocated blue-green infrastructures are typically overlooked by asset managers, which will very likely have detrimental effects on their performance, service life, and wider adoption. In this paper, the working group on Urban Drainage Asset Management (UDAM –https://udam.home.blog/ ) of the IWA and IAHR Joint Committee on Urban Drainage discusses whether the state-of-the-art knowledge based on conventional sewer asset management is sufficient to develop asset management for blue-green infrastructures (BGIs). The discussion is structured around the five preconditions for effective control and asset management. Results show that asset management for BGIs is still underdeveloped due to a lack of monitoring techniques covering the broad range of BGI benefits and performance indicators, inspection techniques covering relevant failure mechanisms and models describing these mechanisms, maintenance and rehabilitation options, and sufficient support tools to aid inhabitants in the operation and maintenance of their individual BGIs such as green roofs or vegetated swales. HIGHLIGHTS: Blue-green infrastructures (BGIs) are widely applied. The asset management of BGI is lacking behind. Monitoring and inspection techniques for BGIs are underdeveloped. Rehabilitation techniques for BGIs are too limited. BGI deterioration models need development.